Dampak Pengetahuan Keuangan, Gaya Hidup dan Akses Fintech terhadap Pengelolaan Keuangan Pribadi pada Generasi Z di Kabupaten Jepara - Naila Maftukha Zamzami; Anna Widiastuti (Jurnal Manajemen dan Organisasi, 2026)
This study aims to analyze the influence of financial knowledge, lifestyle, and access to financial technology (fintech) on the personal financial management of Generation Z in Jepara Regency. The study uses a quantitative approach with a survey method of 173 Generation Z respondents selected using purposive sampling techniques. Data collection was conducted through a questionnaire using a Likert scale, then analyzed using Structural Equation Modeling (SEM) based on SmartPLS. The results show that financial knowledge, lifestyle, and access to fintech have a positive and significant effect on Generation Z's personal financial management. The lifestyle variable proved to have the most dominant influence, indicating that consumption patterns and daily living habits greatly determine the quality of individual financial management. These findings confirm that Generation Z's personal financial management is not only influenced by their level of financial literacy, but also by their lifestyle and use of digital financial technology. Therefore, improving financial literacy and controlling consumptive lifestyles are key to promoting healthier and more sustainable financial management.